(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine the effect of lifestyle and brand image on public interest in using national health insurance (JKN) in Merauke City. This quantitative study has a population in four Merauke Regencies that do not yet have JKN. Data collection was carried out by distributing questionnaires and documentation. The hypothesis test results stated that lifestyle partially affects public interest, where every increase in people’s lifestyle will increase public interest in using National Health Insurance (JKN). Brand image has a partial effect on public interest, meaning that every increase in brand image on National Health Insurance (JKN) will increase public interest. Thus, lifestyle and brand image simultaneously affect public interest in using National Health Insurance (JKN) in Merauke City. Therefore, the study’s results suggest that lifestyle and brand image play crucial roles in influencing public interest in utilizing the National Health Insurance (JKN) in Merauke City. This highlights the importance of considering these factors in promoting and improving the utilization of healthcare services.